An examination of the abandonment of applications for energy efficiency retrofit grants in Ireland. (January 2017) - Collins, Matthew; Curtis, John
Abstract: The Sustainable Energy Authority of Ireland (SEAI) operates the Better Energy Homes (BEH) grant scheme to incentivise residential energy efficiency retrofits, an ongoing scheme which was implemented in 2009. This scheme provides a financial incentive for home owners to engage in energy efficiency retrofits, provided the upgrades meet appropriate energy efficiency standards. This study analyses the BEH data, which is comprised of all applications from March 2009 to October 2015, in order to examine the extent to which applications are abandoned and the determinants thereof. We find that more complicated retrofits are more likely to be abandoned, with variation across certain combinations of retrofit measure. We find lower probabilities of abandonment among certain obligated parties, who are energy retailers obliged by the State to reduce energy consumption in Ireland, while others possess greater likelihoods of abandonment, relative to private retrofits. We find that newer homes are less likely to abandon an application than older homes, as are applications made for apartments, relative to houses. Regional variations exist in abandonment, with rural households more likely to abandon than urban households. A seasonal trend in abandonment is also present, with higher likelihoods of abandonment among applications made during winter. Abstract : Highlights: We use a stated preference approach to model the abandonment of grant applications. Deeper retrofits are more likely to be abandoned, with variation across measures. Abandonment is less likely in applications made via obligated energy suppliers. Regional and Seasonal variations exist in abandonment.